The overlap between epilepsy and Alzheimer's disease and the consequences for treatment. (3rd July 2019) - Powell, Graham; Ziso, Besa; Larner, AJ
ABSTRACT: Introduction : Alzheimer's disease may be associated with both clinical and subclinical epileptic seizure activity. Once regarded as an epiphenomenon, epileptiform activity may, in fact, be an integral part of the Alzheimer's phenotype, and may be not only a symptomatic therapeutic target but also a possible mechanism to retard or prevent disease progression. Areas covered : The authors review clinical research articles with a focus on the semiology, epidemiology, and treatment of seizures in Alzheimer's disease, and also look at some experimental animal model studies which have informed clinical thinking on seizure aetiopathogenesis. The evidence base for treatment decisions is sparse. A brief overview of the clinical assessment of Alzheimer's disease patients considering relevant differential diagnoses and diagnostic pitfalls is presented. Expert opinion : Studies of epileptic seizures in Alzheimer's disease have become more frequent over the last 5–10 years. Understanding of seizure semiology, epidemiology, and possible pathogenesis has increased. However, the optimal management of seizures in this context remains unknown, largely due to the paucity of studies sufficient to examine this question. Clearly, such studies will be required, not only to inform clinicians about symptomatic control of seizures in Alzheimer's disease but also to investigate whether this might impact on disease progression.